PENGARUH CITRA TOKO DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA TERHADAP NIAT BELI ULANG DI TOSERBA SIRANDA SEMARANG - Riana Umi Aziza, 12.05.51.0112; Santosa, M.S. Eric (Students Journal of Economic and Management, 2016)
This study is purposed to analyze the effect of store image and service quality on customer satisfaction and repurchase intention and alos the effect of service quality on repurchase intention at convenience store Siranda. The population is consumer of convenience store Siranda by taking 100 consumers of convenience store Siranda as the sample with non probability sampling technique by purposive sampling. The kind of data that used is primary data which collected direclty from the data collection techniques, ie, by distributing questionnaires. Data that taken from the questionnaire then tested the instrument by validity and reliabityâs test. Then proceed with the data analysis by normality and linearityâs test. Proceed with the classical assumption that include multicollinearity test, heteroscedasticity and autocorrelation. Furthermore, its goodness of fit tested by F test methods, test the coefficient of determination R2 and hypothesis test (t test). The results of this study indicate that the quality of service and the image of the store positive and significant impact on customer satisfaction and repurchase intentions and customer satisfaction as well the positive and significant effect on the repurchasing intentions.Â Key words : store image, service quality, customer satisfaction and repurchase intention